DIFFERENCE OF ACADEMIC ANXIETY REVIEWED FROM AGE ON SEMESTER 8 STUDENTS OF ELEMENTARY SCHOOL TEACHER EDUCATION DEPARTMENT - Ainun Hasri Jannata; Nur'aeni Nur'aeni (PSIMPHONI, 2021)
This research aims to identify the difference of academic anxiety reviewed from age on semester 8 students of the Elementary Teacher Education Department in Universitas Muhammadiyah Purwokerto. The research hypothesis is that there is a difference in academic anxiety reviewed from age on semester 8 students of the Elementary Teacher Education Department in Universitas Muhammadiyah Purwokerto. The 70 research subjects from semester 8 students of Elementary Teacher Education in Universitas Muhammadiyah Purwokerto was taken through incidental sampling. The used scale is an academic anxiety scale. The data were analyzed using T-test with SPSS 22.00 for the Windows program. The result of the hypothesis test shows that the t-count is 3.226,t-table is 1.99547 with p=0.002 (p 0.05). This is strengthened by the average value of academic anxiety of students aged 21-22 years old of 116.89. Meanwhile, the average value of academic anxiety of students aged 23-24 years old of 102.25. The research result shows that there is a difference of academic anxiety reviewed from age on semester 8 students of Elementary Teacher Education Department in Universitas Muhammadiyah Purwokerto.